The association of smoking with drinking pattern may provide opportunities to reduce smoking among students. (2nd January 2016) - Marsh, L; Cousins, K; Gray, A; Kypri, K; Connor, JL; Hoek, J
Abstract : There is evidence that smoking and alcohol consumption are paired behaviours among university students, but we know little about how New Zealand students engage in these behaviours. We estimated prevalence of daily and occasional smoking among university students, and associations of smoking with drinking patterns, demographics and smokefree policies of the university. This research was conducted with 2822 university students, aged 17–25, from five New Zealand universities who participated in an online health survey in 2013. Fourteen percent reported they currently smoke occasionally, and 3% reported smoking on a daily basis. Increasing age, living situation, drinking more often, and drinking more alcohol during drinking occasions were all associated with greater levels of smoking. Understanding patterns of smoking in relation to alcohol consumption may help efforts to further reduce smoking prevalence. Specifically, policy makers should consider approaches that de-couple tobacco and alcohol consumption, such as expanding the smokefree perimeter of bars and disallowing the sale of tobacco at premises licensed to sell alcohol.